2014
DOI: 10.1093/her/cyu012
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of universal campaigns targeting child physical abuse prevention

Abstract: The purpose of this review was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 58 publications
0
51
0
1
Order By: Relevance
“…The majority of the reviews was made up of interventions whose evidence was proven.promising ( n  = 5): this concerned intervention results based on either insufficient statistical power (linked to the fact that the samples were too small) or the fact that it was impossible to draw long-term conclusions from the results [21, 30, 36, 42]. …”
Section: Resultsmentioning
confidence: 99%
“…The majority of the reviews was made up of interventions whose evidence was proven.promising ( n  = 5): this concerned intervention results based on either insufficient statistical power (linked to the fact that the samples were too small) or the fact that it was impossible to draw long-term conclusions from the results [21, 30, 36, 42]. …”
Section: Resultsmentioning
confidence: 99%
“…(25) A meta-analysis of education programmes was conducted to determine non-cognitive developmental benefits of parenting and early childhood education programmes, as this information was not available in existing systematic reviews. The maltreatment review updated the Lancet 2009 series article on prevention of child maltreatment (26) and a systematic review of child maltreatment prevention reviews, (27) by reviewing recent reviews of maltreatment prevention interventions (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)., including home visiting, (28)(29)(30), parenting-training programmes, (31,32) sexual abuse prevention programmes, (33,34) universal campaigns to prevent physical abuse, (35) behavioural and counseling interventions,(36) detection of child maltreatment, (37) and three review studies on prevention of child maltreatment. (38)(39)(40) The social protection review examined five systematic reviews that focused on the effects of social programmes, including conditional and unconditional cash transfers and microcredit schemes.…”
Section: Panel 1: Methods and Search Strategy For Selection Of Intervmentioning
confidence: 99%
“…A systematic review of 12 parenting interventions for reducing harsh/abusive parenting in LMICs found potentially positive results on a range of parenting measures, but the quality of included trials was generally low. (31) Early intervention that occurs prior to the onset of abusive and neglectful parenting is crucial to preventing maltreatment. One specific parenting programme (Triple P) has shown some promise in one HIC RCT.…”
Section: Prevention Of Child Maltreatmentmentioning
confidence: 99%
“…However, a focus on primary prevention of ACEs, in which the incidence of ACEs is reduced at the population level, will have the greatest individual and societal impact (52,53). In order to accomplish this, the interventions should focus on strengthening individual and community resilience rather than solely identifying and responding to individual ACEs by strengthening communities and reducing resource disparity.…”
Section: Approaches To Reducing the Burden Of Acesmentioning
confidence: 99%